Fangstmannsbiografien og heltelitteratur. Med et skråblikk på sjangeren: Wanny Woldstad, Henry Ette, Thorleif Bjertnes og Henry Rudi. - Karlsen, Silje Solheim (Nordlit, 2014)
This article deals with the literature written by hunters and trappers wintering on Svalbard, addressing especially the idea of the hunter´s memoirs as heroic literature. My reading is centered around Wanny Woldstads account Første kvinne som fangstmann på Svalbard (1956) and against the background of memoirs written by Henry Rudi, Henry Ette and Thorleif Bjertnes I first question the label heroic, before I proceed examining how Woldstad with her female perspective relates to the traditional view on the hunter as a masculine, hard-boiled Arctic hero.